The Influence of Work Discipline, Motivation and Work Environment on the Performance of Mining Supervisors at PT. Cristian Eka Pratama, East Kalimantan - Aditya Aditya; Fathurrahman Fathurrahman; Murtianingsih Murtianingsih (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This research examines the influence of work discipline, motivation, and work environment on the performance of mining supervisors at PT. Cristian Eka Pratama, East Kalimantan. The mining industry in Indonesia has experienced rapid growth, especially in Kalimantan, which is rich in coal reserves. Given the important role of mining supervisors, this study aims to analyze how work discipline, motivation, and work environment affect supervisor performance. This research is crucial as mining supervisors face high-risk work environments and must adhere to safety standards while managing daily operations. The study uses quantitative methods with multiple linear regression analysis to explore how these factors—work discipline, motivation, and work environment—contribute to performance. Data were collected through surveys and analyzed to determine the impact of these factors on performance. The results of the study show that work discipline, work motivation, and work environment have a significant impact on supervisor performance. It is expected that these results will provide valuable insights into improving human resource management in the mining sector, particularly in enhancing supervisor performance.